Changes in the Soil Phosphorus Supply with Rice Straw Return in Cold Region - Shuangshuang Yan; Chunxue Liu; Jianan Li; Jinwang Li; Can Cui; Jinsheng Fan; Zhenping Gong; Zhongxue Zhang; Chao Yan (Agronomy, 2023)
Most phosphorus (P) in soil exists in nonlabile forms, leading to poor soil P supply capacity and limiting crop growth. This study evaluated the effect of 10 years of rice straw return on rice yield, soil P budget, P fractions, and phosphatase activity to establish the relationship between soil P fractions and related microbial communities. Four treatments, i.e., no rice straw return (S0), low amount of rice straw return (S1), high amount of rice straw return (S2), and abandoned farmland (AL), were used in the evaluation. The results showed that rice straw return had no effect on the rice yield and P uptake, and the P budget was positive in the S2 treatment. Rice straw return increased the phosphatase activity and content of soil Olsen-P, total P, NaHCO3-, and NaOH-extractable P, and the phosphatase activity and P fractions were both increased with the amount of straw returned. There was a positive correlation between most soil P fractions and active organic carbon fractions. Rice straw return changed the composition and abundance of soil phosphate-solubilizing bacteria (PSB). The findings showed that straw return decreased the proportion of soil nonlabile P, enhancing the soil P supply capacity, and they further showed that the abundance of PSB was not consistent with soil P content.